Strategi Visualisasi dan Narasi Digital dalam Promosi Wisata Edukasi di Indonesia: Analisis Konten Instagram Bertagar #wisataedukasi - Rachmaniar Rachmaniar; Renata Anisa (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This article discusses the visual and narrative strategies used in promoting educational tourism for children in Indonesia through Instagram posts with the hashtag #wisataedukasi. The research adopts a qualitative approach with content analysis of both visual and narrative aspects of digital posts showcasing educational tourist destinations suitable for families. The aim of the study is to understand how visual and narrative elements work together to shape the audience's perception of educational tourism destinations. The findings show that the visual content in the Instagram posts is dominated by the use of bright colors, cheerful expressions of children, and participatory educational activities. These activities involve direct interaction with nature or animals, such as feeding animals or conducting simple experiments, designed to create a fun learning experience for children. Narratively, captions tend to use casual and consultative language, with word choices emphasizing excitement, togetherness, and the educational benefits that can be gained from visiting these destinations. The representation of the complete family in the content plays an important role in building the image of educational tourism as a space that supports quality family time. Additionally, the use of relevant and popular hashtags strengthens the association of educational tourism destinations with modern parenting, which emphasizes learning while playing. This visual and narrative strategy has been proven effective in building emotional engagement with the audience and creating a positive perception of educational destinations. Overall, this article concludes that social media, particularly Instagram, plays a significant role in shaping the branding of educational tourism. It is therefore recommended to continue strengthening visual and narrative content strategies tailored to the preferences of young families as the primary target for promoting children's educational tourism.